Internet of Things in organisations: artefactual characteristics that influence adoption - Tshilenge, Henry Busaka (Department of Information Systems, 2026)
Background: The Internet of Things (IoT) has gained significant attention from businesses and academia. IoT promises are ambitious: creating, collecting, and sharing information independently of time, place, and motion. Things are rendered autonomous, able to identify themselves, network with other objects, and analyse the data they produce. IoT systems are used in some organisations to improve efficiency and facilitate trade in commodities and services. These systems help prevent errors, monitor operations, track assets, deter theft, and integrate complex systems through real-time data collection and analysis. Problem Statement: IoT promises many benefits, which are already tangible in the agriculture, logistics, retail, and supply chain sectors. However, some organisations still adopt IoT hesitantly, while others still hold a conservative stance. Little is known about its adoption in organisations based on its artefactual characteristics. Purpose: This study explores the artefactual characteristics of the Internet of Things that lead to its adoption and implementation in organisations. The focus is on the impact of identified IoT characteristics on its adoption as reflected by the continuance intention. Methodology: The study adopted a quantitative survey strategy and collected data via the Academic Prolific Online Panel1, with a sample of 293 participants from South Africa, the United Kingdom, and the United States. Findings: The results indicate that IoT characteristics closely aligned with business needs, such as relative advantage (profitability), Compatibility (alignment with values), seamless integration, and self-adaptation (intelligent, efficient operation and future growth), significantly influence IoT adoption as reflected by the continuance intention in organisations. The study went beyond the traditional Technology-Organisational-Environment (TOE) framework technology characteristics adapted from the Diffusion of Innovation framework, such as relative advantage, complexity, and compatibility. In addition, the findings revealed that integration and self-adaptation (i.e., intelligence) significantly influence technology adoption, as reflected by continuance intention. The research contributes to the knowledge of IoT. The study recommends that future research look further into the technocentric characteristics such as connectivity, security and interoperability, which were unexpectedly found not to influence adoption as reflected by the continuance intention.